Implementasi Game Edukasi 3D dalam Pembelajaran Bahasa Jepang pada Mahasiswa Universitas Almuslim dengan Unity Engine Menggunakan Metode Multimedia Development Life Cycle (MDLC) - Sarah Nadia; Riyadhul Fajri; Sriwinar (Jurnal Ilmu Komputer Aceh, 2026)
This study aims to develop a 3D educational game as an interactive learning medium for Japanese language learning at Universitas Almuslim using the Multimedia Development Life Cycle (MDLC) method and Unity Engine. The research employs six MDLC stages: concept, design, material collecting, assembly, testing, and distribution. The game, entitled "Nihongo Quest," presents N5-level Japanese vocabulary and characters (Hiragana and Katakana) within an interactive 3D environment. The development utilized Blender for 3D asset modeling, Visual Studio Code for C# scripting, and Universal Render Pipeline (URP) for visual optimization. System testing was conducted using black box testing across 10 functional features. The results show that all tested features passed successfully, demonstrating that the game functions as intended. The game provides an interactive and engaging learning experience, making it a viable alternative learning medium for students who struggle with traditional Japanese language instruction.